The effect of palm oil fuel clinker powder and cockleshell powder as cement replacement on durability properties of the concrete mortar - A. A., Qasem; M. A., Al-Mekhlafi; F. M., Yahaya (IOP Publishing Ltd, 2021)
The concepts of eco-friendly building are getting more attention today. The standard materials of concrete that used such as cement and aggregate are not totally environmentally friendly. Thus, many materials from natural sources can be an alternative to the realization of the green building concept. As a result, many researchers have devoted their attention towards identifying eco-friendlier substitutions to be used in concrete. This study was conducted to investigate the efficiency of two different types of waste materials which are palm oil clinker (POC) and cockle shell (CS) as partial replacement of cement on durability aspects. The POC and CS materials were ground to achieve a small particle size to fit with the concrete mix as cement replacement. The replacement of cement was at different levels (10% and 20%). Six mix proportions were made with different percentage of palm oil clinker powder POCP and cockle shell powder CSP. The specimens were cured by immersing in water for 7 and 28 days. The tests that were conducted were acid resistance test and water absorption test. Therefore, the experiment result showed that the POC had a negative impact to the concrete in both tests while the CSP proved it is resistance to acid.